2016
DOI: 10.1007/978-3-319-47413-7_24
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Thresholds for Anomaly-Based Intrusion Detection in Dynamical Environments

Abstract: Abstract. In cyber-physical systems, malicious and resourceful attackers could penetrate a system through cyber means and cause significant physical damage. Consequently, early detection of such attacks becomes integral towards making these systems resilient to attacks. To achieve this objective, intrusion detection systems (IDS) that are able to detect malicious behavior early enough can be deployed. However, practical IDS are imperfect and sometimes they may produce false alarms even for normal system behavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 20 publications
0
20
0
Order By: Relevance
“…A simple way to combat the difficulty of threshold setting is by using multiple thresholds, representing varying degrees of confidence. Advanced threshold setting models such as Laszka et al (2016) and Ghafouri et al (2016) can be coupled with the proposed VAE model in future studies for optimal threshold setting. Ghafouri et al (2016) used a game-theoretic setup to solve the problem of finding time-varying optimal detection thresholds in dynamical environments, with a numerical demonstration on water distribution systems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A simple way to combat the difficulty of threshold setting is by using multiple thresholds, representing varying degrees of confidence. Advanced threshold setting models such as Laszka et al (2016) and Ghafouri et al (2016) can be coupled with the proposed VAE model in future studies for optimal threshold setting. Ghafouri et al (2016) used a game-theoretic setup to solve the problem of finding time-varying optimal detection thresholds in dynamical environments, with a numerical demonstration on water distribution systems.…”
Section: Discussionmentioning
confidence: 99%
“…Advanced threshold setting models such as Laszka et al (2016) and Ghafouri et al (2016) can be coupled with the proposed VAE model in future studies for optimal threshold setting. Ghafouri et al (2016) used a game-theoretic setup to solve the problem of finding time-varying optimal detection thresholds in dynamical environments, with a numerical demonstration on water distribution systems. The new mechanism can also use a secondary set of data (e.g., the BATADAL Training Dataset #2, which is found in Taormina et al 2018) for evaluation and adjustment of the optimal thresholds found.…”
Section: Discussionmentioning
confidence: 99%
“…e paper shows that computing optimal a acks and defenses is computationally expensive, and proposes heuristic algorithms for computing near-optimal strategies. Further, the work in [6] studies the problem of nding optimal thresholds for anomaly-based detectors implemented in dynamical systems in the face of strategic a acks. e paper provides algorithms to compute optimal thresholds that minimize losses considering best-response a acks.…”
Section: Related Workmentioning
confidence: 99%
“…In (Ghafouri et al, 2016), the authors find the optimal threshold, using an exhaustive search, for anomaly-based intrusion detection in dynamical environments, but this is done based on the strong assumption that the expected damage incurred by a system from an undetected attack at any instant in time is known. This is a common problem with binary intrusion detection approaches.…”
Section: Introduction and Related Workmentioning
confidence: 99%